The beneficial effects of probiotics on patients with coronary heart disease: a systematic review and meta-analysis - Dong, Jie; Chen, Lei; Zheng, Nan; Yang, Ming (Frontiers in Nutrition, 2025)
BackgroundCoronary heart disease (CHD) is a major global health burden, and emerging evidence suggested that probiotics could improve cardiovascular health by modulating gut microbiota and lipid profiles. However, the efficacy of probiotics remains elusive, indicating the necessity of conducting this meta-analysis.MethodsThis study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, searching PubMed, EMBASE, and Web of Science databases for retrieving randomized controlled trials (RCTs) on probiotics’ effects on lipid profiles (low-density lipoprotein (LDL), high-density lipoprotein (HDL), and triglycerides (TG)) in CHD patients. Inclusion and exclusion criteria concentrated on English-language RCTs, and data on study characteristics were extracted. Study quality was assessed using Cochrane and NHLBI tools, and statistical analysis was conducted via R 4.3.2 software.ResultsThe literature search identified 263 records, yielding 6 RCTs, 5 of which were included in the meta-analyses. For LDL level (n = 278), both fixed-effects and random-effects models exhibited an overall effect size of 1.25 units [95% confidence interval (CI): −0.62 to 3.12] with a low heterogeneity (I2 = 0%), while probiotics-based monotherapy achieved a mean difference (MD) of 13.4105 (95% CI: −8.0670 to 34.8879) versus an MD of 1.1578 for combination therapy (95% CI: −0.7146 to 3.0302). For HDL level (n = 278), the fixed-effects model yielded an MD of −3.8107 (95% CI: −4.2490 to −3.3724) versus an MD of −2.3119 for the random-effects model (95% CI: −4.2290 to −0.3949) with a moderate heterogeneity (I2 = 61.6%). Combination therapy demonstrated an MD of −2.9848 (95% CI: −4.7965 to −1.1732), while monotherapy exhibited a non-significant MD of 0.9115 (95% CI: −3.5084 to 5.3314). TG analysis yielded a common effect size of 17.95, with a minimal-to-moderate heterogeneity (I2 = 0 to 84.7%).ConclusionProbiotics, particularly monotherapy for LDL and combination therapy for HDL, exhibited potential to improve lipid profiles in CHD patients. However, further research is needed to address existing limitations and confirm efficacy.